The Trade-Off between Dietary Salt and Cardiovascular Disease; A Role for Na/K-ATPase Signaling? - Xie, Joe X.; Shapiro, Anna Pearl; Shapiro, Joseph Isaac (Frontiers in Endocrinology, 2014)
It has been postulated for some time that endogenous digitalis-like substances, also called cardiotonic steroids (CTS), exist, and that these substances are involved in sodium handling. Within the past 20 years, these substances have been unequivocally identified and measurements of circulating and tissue concentrations have been made. More recently, it has been identified that CTS also mediate signal transduction through the Na/K-ATPase, and consequently been implicated in profibrotic pathways. This review will discuss the mechanism of CTS in renal sodium handling and a potential “trade-off” effect from their role in inducing tissue fibrosis.